(untitled) (Al-Academy, 2024)
Traditional interior spaces in Arab and Islamic architecture are characterized by their unique character that reflects local culture and heritage, and include a wide range of places inside traditional homes and buildings, and the traditional guest lounges, which are also known as additives in Iraq and councils or diwaniyas in some Arab countries, are among the most important, which are places dedicated to receiving guests and gatherings of family and friends, and reflect an aspect of authentic Arab hospitality, The designs and styles of these galleries vary according to different local cultures and traditions, the current research consists of a systematic framework consisting of a problem, which is the following question: What is the extent to which cultural and social factors affect the design performance of the interior spaces of the local reception rooms? The aim of the current research is to: Reveal the reality of the state of designs of traditional reception spaces and the references of their design, And find design pillars for traditional reception spaces in a way that contributes to enhancing the sense of social harmony between those spaces and the privacy of their patrons. And the procedures of his research, which followed the descriptive approach and the research reached the results: as the researcher analyzed according to the form prepared in advance and reached the results statistically proven the arithmetic mean of the paragraphs of the form 3.27 and the percentage rate of all paragraphs 81.9%, and the conclusions concerned: